Group A Streptococcal vaccine candidate: contribution of epitope to size, antigen presenting cell interaction and immunogenicity. (December 2014) - Zaman, Mehfuz; Chandrudu, Saranya; Giddam, Ashwini K; Reiman, Jennifer; Skwarczynski, Mariusz; McPhun, Virginia; Moyle, Peter M; Batzloff, Michael R; Good, Michael F; Toth, Istvan
Aim: Utilize lipopeptide vaccine delivery system to develop a vaccine candidate against Group A Streptococcus .Materials & methods: Lipopeptides synthesized by solid-phase peptide synthesis-bearing carboxyl (C)-terminal and amino (N)-terminal Group A Streptococcus peptide epitopes. Nanoparticles formed were evaluated in vivo .Results: Immune responses were induced in mice without additional adjuvant. We demonstrated for the first time that incorporation of the C-terminal epitope significantly enhanced the N-terminal epitope-specific antibody response and correlated with forming smaller nanoparticles. Antigen-presenting cells had increased uptake and maturation by smaller, more immunogenic nanoparticles. Antibodies raised by vaccination recognized isolates.Conclusion: Demonstrated the lipopeptidic nanoparticles to induce an immune response which can be influenced by the combined effect of epitope choice and size.